AN ASSESSMENT OF TOURIST SATISFACTION LEVELS WITH REGARD TO ATTRACTIONS, AMENITIES, ACCESSIBILITY, AND ANCILLARY SERVICES IN CUNCA WULANG - Putri, Natalia Selviana; Rudiyanto, Roseven; Sandrio, Laurensius; Seran, Marius Yosef (Jurnal Hospitality dan Pariwisata, 2026)
Tourist satisfaction is one of the evaluation results of tourism facilities provided by tourism managers. This is to determine the quality of a tourist destination for visiting tourists. Therefore, the purpose of this study was to measure the level of tourist satisfaction with attractions, amenities, accessibility, and ancillary facilities at Cunca Wulang Waterfall. This study used a quantitative approach. The data collection technique used in this study was a questionnaire distributed to tourists visiting Cunca Wulang Waterfall. Data collected from 150 respondents. The results showed that tourist satisfaction with the 4A aspects of Cunca Wulang Waterfall was in the satisfactory category. However, several aspects needed improvement, such as toilets, the addition of ropes to the pedestrian bridge, the addition of directional signs, and cleaning the roadside for public transportation access.